Catalytic conversion of greenhouse gases - Osazuwa, Osarieme Uyi; Cheng, Chin Kui (Elsevier, 2020)
Greenhouse gases with specific focus on CH4 and CO2 have significantly being the root cause of severe green and environmental issues like global warming and climate change. In recent times, attention has been channelled to the reforming of these gases to products of higher demand by catalytically-driven process. Hence, catalytic conversion of greenhouse gases have been analysed with specific focus on the conversion process which include steam reforming, partial oxidation reforming, CO2 reforming and combined reforming. In addition, the reforming process has also been discussed on the basis of catalyst type to include supported metallic catalyst, promoted metallic catalyst and perovskite catalyst. In order to clearly explain the process, the kinetics of the reforming process and catalyst deactivation have been reviewed with CO2 reforming of CH4 as the case study.